Personal study, peer engagement and learning infrastructure access during Covid-19 shock : implication for rural based-university students’ in 4IR - Kemi, Megbowon Funmilola; Chijioke, Uwah (Penerbit Universiti Kebangsaan Malaysia, 2021)
Covid-19 pandemic has not only affected educational outcomes of students’, it also has an impact on the elements that enhance learning. The purpose of this study is to examine students’ experiences relating to factors that influence learning outcomes, during the inevitable remote learning. Consequently, a qualitative research method was adopted and data was obtained through an open-ended questionnaire from students in one South African University. The data obtained were analyzed using thematic analysis. From the analysis, the identified themes include, personal study, peer engagement, and learning infrastructure access during the inevitable remote learning. The study reveals that personal study is being affected due to the unfavorable study environment of the students. Furthermore, unstable and inadequate access to intangible learning infrastructural facilities such as electricity and internet connection are identified as challenges to remote learning. Generally, the study voices the existing socioeconomic, digital, and geographical inequalities in the South African space which should be adequately addressed. The study concludes that in order not to leave any student behind in terms of higher education training, absolute adoption of 4IR technologies for learning might be impracticable. Furthermore, since face to face learning is indispensable, adoption and implementation of blended or hybrid teaching and learning techniques, and on-campus digital training by rural based universities become imperative, as this will equip students with digital skills needed for post-school labour market.